Strategi pengembangan kompetensi guru pendidikan agama Khonghucu di Jawa Timur: Membangun harmoni dalam indahnya moderasi - Abshor, Mokhammad Ulil (Maliki Interdisciplinary Journal, 2024)
The research aims to eplore effective strategies in developing the competence of Confucian religious education teachers in East Java, with a focus on building harmony in moderation practices. This research fins and analyses various approach to increasing the competence of Confucian religious education teachers through literature studies and reviews of related literature. This study provides in-dept insight into various methods that can be used to improve the quality of Confucian religious teaching. These methods include pedagogical skill development, training, collaborative learning, and implementation of Confucian values in the Curriculum. In addition, this research show how important it is to strengthen Confucian religious identity in maintaining the principle of medoration in religious education. The results of this research indicate that professionalism of Confucian religious education teacher should be based on a strong understanding of the local contect dan Confucian values, wjile still prioritizing inclusive and harmonious values in education.